Evaluation of a professional development model for enhancing knowledge,skill and confidence in dysphagia management - Rahayu Mustaffa Kamal; Ward, Elizabeth Celeste; Cornwell, Petrea Lee (Penerbit Universiti Kebangsaan Malaysia, 2017)
There were critical limitations to dysphagia services in Malaysia with speech-language pathologists’ (SLPs) reported lacking skills and confidence in managing the disorder. This study examined the impact of providing professional development training in dysphagia management. Aims were to determine if: (1) delivery of a training series enhances SLPs knowledge in dysphagia management, (2) knowledge translated into improved clinical skills and (3) clinicians’ perception of their knowledge, skills and confidence improved post-training. The study used a single cohort pre- and post-test research design and involved nine Malaysian SLPs. Participants underwent assessment at pre- and immediately post-training and again at one month post-training. At each assessment level, knowledge and skills were assessed via a written examination and observational assessment of clinical performance respectively. Visual analogue scales were used to measure clinician’s perceptions of knowledge, skills and confidence. The training model involved four consecutive; 4-hour week-end workshops with opportunity to apply new knowledge and develop networking in clinical practice in the weekdays between each session. Significant (p < 0.05) improvements in knowledge and clinical skills were observed immediately post- and at one month after training. Clinician’s perceptions of knowledge, skills and confidence were also significantly higher immediately post- and at one month post-training. The current 4-week structured professional development model was found to be effective in enhancing SLPs’ knowledge and skills in dysphagia management and improving their perceptions and confidence. The findings highlight the benefits that can be achieved through well designed professional development programs.